Covert Communication With Uninformed Backscatters in Hybrid Active/Passive Wireless Networks: Modeling and Performance Analysis - Ma, Wenyuan; Niu, Zhiang; Wang, Wei; He, Shiyue; Jiang, Tao (IEEE transactions on communications, 2022)
In this paper, we propose a new framework for covert communication in hybrid active/passive networks, which explores the inherent uncertainty of the backscatter transmissions to achieve active and passive communication reciprocity in security. Under this framework, we first model the aggregate interference from the sporadic backscatter transmissions and derive the covert outage probability and the transmission success probability to capture the covertness and reliability. Then, we formulate a transmit power optimization problem to maximize the covert throughput subject to certain covertness and reliability requirements and derive a closed-form approximation of the maximum covert throughput. Particularly, we investigate the worst-case scenario of covert communication in which warden always uses the optimal detection thresholds. Finally, numerical results demonstrate that covert communication with the help of uninformed backscatters that are not coordinated with Alice in the hybrid network is feasible. Results also provide design guidelines for the optimal choice of interference parameters, which is capable of striking a balance between covertness and reliability.